Etika guru di tengah budaya ‘Viral’ dan tuntutan konten edukatif di media sosial - Nugraha, Awang Aji (Maliki Interdisciplinary Journal, 2025)
The phenomenon of teachers actively becoming educational content creators on social media has become a new trend in education. However, popularity and viral culture bring specific challenges to professional ethics. This literature review aims to examine how teacher ethics must remain upheld amid digitalization, social media presence, and the desire to appear appealing to the online public. This study uses a descriptive qualitative approach through literature analysis from various journals, books, and teacher code of ethics documents. The findings indicate that social media can be a means to strengthen teacher professionalism if used ethically, but it can also become a trap of ego and ethical violations if not used wisely.